The Influence of Profitability, Carbon Emission Disclosure, and Green Accounting on Stock Returns of Energy Sector Companies Listed on the IDX - Kevin Dylan Halim; Gerianta Wirawan Yasa (International Journal of Economics, Management and Accounting, 2025)
Stock return refers to the level of profit gained by investors from stock ownership. The volatility of a company's stock return can be influenced by financial information such as profitability. However, over time, there has been growing pressure on companies not only to pursue financial profit but also to consider non-financial information, such as carbon emission disclosure and green accounting. This study aims to empirically examine the effect of profitability, carbon emission disclosure, and green accounting on the stock returns of energy sector companies. The research was conducted on energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The sample was selected using a non-probability sampling method with a purposive sampling technique, resulting in 39 companies and a total of 117 observations. Data were collected using a non-participant observation method, and the data were analyzed using multiple linear regression analysis. During the data analysis stage, outliers were detected in the dependent variable, which affected the results of the normality and heteroskedasticity tests. To address this, the winsorizing method was employed to minimize the influence of outliers without eliminating the data. The findings indicate that profitability (measured by ROA), carbon emission disclosure, and green accounting all have a positive effect on stock returns. The implications of this study provide empirical evidence on the influence of profitability, carbon emission disclosure, and green accounting on stock returns in the energy sector on the IDX during the 2021–2023 period. Furthermore, the findings offer valuable insights for corporate management to enhance transparency on sustainability issues, provide strategic guidance for investors, and raise public awareness on the importance of supporting environmentally friendly businesses.